Synthesis of aliphatic nitriles from cyclobutanone oxime mediated by sulfuryl fluoride (SO2F2) - Chen, Xian-Lin; Qin, Hua-Li (Beilstein Journal of Organic Chemistry, 2023)
A SO2F2-mediated ring-opening cross-coupling of cyclobutanone oxime derivatives with alkenes was developed for the construction of a range of δ-olefin-containing aliphatic nitriles with (E)-configuration selectivity. This new method features wide substrate scope, mild conditions, and direct N–O activation.
Keywords: direct N–O activation; E-selectivity; nitrile synthesis; ring-opening cross-coupling; sulfuryl fluoride; SO2F2